Mathematical modeling of canonical and non-canonical NF-κB pathways in TNF stimulation. (November 2020) - Ji, Bing; Zhang, Yao; Zhen, Changqing; Fagan, Michael J; Yang, Qing
Highlights: The NF-κB signaling consists of the canonical and non-canonical pathway. The non-canonical NF-κB pathway is regulated by the canonical pathway through TRAF1|NIK after stimulated by TNF. The model can simulate the canonical and the non-canonical NF-κB pathway. The model investigates the mechanism in which the non-canonical pathway is regulated by the canonical pathway after stimulated by TNF. Abstract: Background and objective: NF-κB can be activated by the canonical and non-canonical pathways. These two pathways interplay via the TRAF1|NIK complex after stimulation by TNF. However existing mathematical models of two pathways are inadequate. In this context, an improved mathematical model is constructed to simulate these two pathways and their coupling stimulated by TNF. Methods: A schematic description of two NF-κB pathways and their relation after TNF stimulation is constructed at first. Then twenty-eight ordinary differential equations are utilized to build the mathematical model. Model equations are solved via the ordinary differential equation solver (ode23). Results: The proposed model firstly reconstructs the changes in concentrations of NF-κB pathway related biochemical factors with time, and further investigates the underlying mechanism of interaction between two pathways through the TRAF1|NIK complex after stimulation. Conclusions: The model is validated through good agreement between simulation results and published experimental observations. This study helps to well understand the canonical and non-canonical pathways and their interaction. It also provides a potential tool to investigate how the dysregulated pathways act in pathological conditions.